Left ventricular function after ultra-distance triathlon : response is dependent on the cardiac loading conditions - Hassan, Muhammad Yusuf (MRC/UCT RU for Exercise and Sport Medicine, 2017)
The purpose of this thesis is to establish if there is any evidence to support the hypothesis that altered ventricular loading conditions after the cessation of exercise may cause "cardiac fatigue". The studies that have shown post-exercise "cardiac fatigue" have not controlled for either preload or afterload or both, before and after exercise. These studies may rather have identified the effects of alterations in peripheral vascular function on left ventricular function after prolonged exercise. The research study in this thesis is to evaluate if the loading conditions of the heart affect the echocardiographic measurements after exercise that may be misinterpreted as "cardiac fatigue". Echocardiography as a tool of cardiac evaluation cannot be done during exercise because of the technical difficulty of doing a cardiac ultrasound on a human being in motion. The studies that have investigated post exercise "cardiac fatigue" have therefore measured cardiac function after exercise and retrospectively assumed that the cardiac dysfunction was present during exercise since the cardiac demands are at their peak during exercise. However, the post exercise period may be associated with altered loading conditions that may cause changes in the echocardiographic measurements that are similar to cardiac abnormalities.